Pengaruh Penambahan LPG (Liquified Petroleum Gas) pada Proses Pembakaran Premixed Uap Minyak Jarak Pagar (Jatropha Curcas L.) terhadap Warna dan Temperatur Api - Defmit B. N. Riwu (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2016)
This study was conducted to determine the effect of the addition of Liquefied Petroleum Gas (LPG) to the premixed combustion characteristics of Jatropha oil vapor. Combustion characteristics studied were the color of fire and flame temperature. In this study, using a variation of the composition of LPG as much as 0%, 10%, 20%, 30%, and 40% of the total mass flow of steam Jatropha oil, while the air discharge varied from 0 ml/min to blow off with multiples of 20 ml/min. In oil discharge distance is kept constant yawning as much as 0046 ml/min, from the results, there is a section on the burning diffusion flame in blue and yellow. The yellow color indicates the burning fuel diffusion and the formation of soot, and in the middle of the blue flame. Increasing the flow of air at constant fuel flow, flame yellow part is getting a bit and part blue flame sees more. In particular, equivalence ratio looked two parts of the cone of fire. The cone fire inside bright blue is a premixed flame, while the outer cone of blue flame thins a diffusion flame. If the percentage of LPG increased, fire temperature will also increase. The lowest temperature to highest temperature, respectively are in the middle of the fire, the edge of the fire, and the peak of the fire.